Flexible, environmentally-acceptable and long-durable-energy-efficient novel WS2–polyacrylamide MOFs for high-performance photodetectors. Issue 9 (6th April 2022) - Verma, Arpit; Chaudhary, Priyanka; Tripathi, Ravi Kant; Yadav, B. C.
Abstract : In this work, two-dimensional WS2 –polyacrylamide metal–organic frameworks (MOFs) are prepared via an energy-efficient solvent-free frontal polymerization method and further used as a biocompatible, flexible, and low threshold high-performance photodetection. Abstract : In this work, two-dimensional WS2 –polyacrylamide metal–organic frameworks (MOFs) are prepared via an energy-efficient solvent-free frontal polymerization method and further used as a biocompatible, flexible, and low threshold high-performance photodetection. For fabricating biocompatible and flexible photodetector devices, these MOFs are coated on a normal paper substrate and carbon nanotubes are used as the electrodes. Scanning and tunneling electron microscopy (SEM and TEM) images exhibit the nanosheet-like structure and clear incorporation of WS2 nanosheets in a polyacrylamide matrix. X-ray photoelectron spectroscopy (XPS) analysis shows the peaks of W 5p3/2, W 4f3/2, and W 4f7/2 at the binding energies of 38.48, 34.98, and 32.88 eV, confirming the presence of W with a valence of +4. Further investigations on MOFs were carried out through UV-Visible spectroscopy, Raman spectroscopy, Fourier transform infrared spectroscopy (FTIR), dynamic light scattering (DLS), and differential scanning calorimetric (DSC) analysis. This environmentally acceptable device shows the very appreciable responsivity and detectivity of 1.3742 A W −1 and 1.5268 × 10 12 Jones, respectively. The highest external quantum efficiency (EQE) and linear dynamic range (LDR) were found to be 465.935% and 28.6725 dB, respectively, with the noise equivalent power (NEP) of 3.6845 × 10 −8 W.